2019
DOI: 10.1177/1756286419855485
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging markers of clinical progression in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Background: One of the main goals of novel, noninvasive imaging techniques like high-resolution nerve ultrasound (HRUS) and corneal confocal microscopy (CCM) is the prediction of treatment response for patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods: A total of 17 patients with CIDP were examined prospectively at baseline and every 9 months over a period of 18 months using CCM to quantify corneal nerve degeneration markers and immune cell infiltration as well as HRUS to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
(64 reference statements)
4
21
0
Order By: Relevance
“…HRUS is a recently developed imaging method which very precisely detects morphological alterations of peripheral nerves 21 . We applied HRUS technology for the in vivo examination in peripheral nerves in PD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRUS is a recently developed imaging method which very precisely detects morphological alterations of peripheral nerves 21 . We applied HRUS technology for the in vivo examination in peripheral nerves in PD.…”
Section: Resultsmentioning
confidence: 99%
“…HRUS is a recently developed imaging method which very precisely detects morphological alterations of peripheral nerves. 21 We applied HRUS technology for the in vivo examination in peripheral nerves in PD. First, we examined entrapment sites where peripheral nerve pathology can be pronounced because of constantly higher mechanical burden.…”
Section: Morphologic Variability Of Nerve Pathology In High-resolutiomentioning
confidence: 99%
“…The benefit of nerve ultrasound in the diagnosis of CIDP has been proven several times over the past 7 years, but it is still not established as standard diagnostic criterion. The measurement of cross-sectional area (CSA) in ultrasound correlates well to CSA detected by MRI and with the nerve T2-weighted signal intensity [26][27][28]. Morphological changes like swollen, hypoechogenic nerve and fascicles detected in ultrasound represent acute inflammation [29,30], while hyperechogenic nerves rather are supposed to occur in case of fibroid remodeling and axonal damage [29,31].…”
Section: Nerve Ultrasoundmentioning
confidence: 66%
“…It is currently still unclear whether these parameters change dynamically in the course of the disease. Moreover, corneal nerve fibers are surrounded by immune cell populations, which can easily be quantified and change dynamically during disease course and might correlate with disease activity [28].…”
Section: Corneal Confocal Microscopymentioning
confidence: 99%
“…More recently, we have shown an increase in corneal dendritic cells in individuals with CIDP and suggested that this may help to stratify CIDP subtypes, clinical course, and disease activity [ 23 ]. In a prospective study of 17 individuals with CIDP who were followed over 18 months, the presence of > 30 cells/mm 2 at baseline identified clinical progression with a sensitivity and specificity of 100% [ 24 ]. Moreover, in one person with anti-neurofascin-155 neuropathy, treatment with rituximab was associated with a reduction in the serum antibody titer with a clinical and electrophysiological improvement and reduction of corneal inflammatory cell infiltrates [ 25 ].…”
Section: Introductionmentioning
confidence: 99%